Asymmetric Optical Transitions Determine the Onset of Carrier Multiplication in Lead Chalcogenide Quantum Confined and Bulk Crystals - Spoor, Frank C. M.; Grimaldi, Gianluca; Delerue, Christophe; Evers, Wiel H.; Crisp, Ryan; Geiregat, Pieter; Hens, Zeger; Houtepen, Arjan J.; Siebbeles, Laurens D. A. (Acs Nano, 2018)
Carrier multiplication is a process in which one absorbed photon excites two or more electrons. This is of great promise to increase the efficiency of photovoltaic devices. Until now, the factors that determine the onset energy of carrier multiplication have not been convincingly explained. We show experimentally that the onset of carrier multiplication in lead chalcogenide quantum confined and bulk crystals is due to asymmetric optical transitions. In such transitions most of the photon energy in excess of the band gap is given to either the hole or the electron. The results are confirmed and explained by theoretical tight-binding calculations of the competition between impact ionization and carrier cooling. These results are a large step forward in understanding carrier multiplication and allow for a screening of materials with an onset of carrier multiplication close to twice the band gap energy. Such materials are of great interest for development of highly efficient photovoltaic devices.
Keywords: quantum dot; carrier multiplication; carrier cooling; threshold energy; transient absorption spectroscopy; tight-binding calculations